Female and male mice have differential longterm cardiorenal outcomes following a matched degree of ischemia–reperfusion acute kidney injury - Soranno, Danielle E.; Baker, Peter; Kirkbride-Romeo, Lara; Wennersten, Sara A.; Ding, Kathy; Keith, Brysen; Cavasin, Maria A.; Altmann, Christopher; Bagchi, Rushita A.; Haefner, Korey R.; Montford, John; Gist, Katja M.; et al. (Scientific reports, 2022)
Acute kidney injury (AKI) is common in patients, causes systemic sequelae, and predisposes patients to long-term cardiovascular disease. To date, studies of the effects of AKI on cardiovascular outcomes have only been performed in male mice. We recently demonstrated that male mice developed diastolic dysfunction, hypertension and reduced cardiac ATP levels versus sham 1 year after AKI. The effects of female sex on long-term cardiac outcomes after AKI are unknown. Therefore, we examined the 1-year cardiorenal outcomes following a single episode of bilateral renal ischemia–reperfusion injury in female C57BL/6 mice using a model with similar severity of AKI and performed concomitantly to recently published male cohorts. To match the severity of AKI between male and female mice, females received 34 min of ischemia time compared to 25 min in males. Serial renal function, echocardiograms and blood pressure assessments were performed throughout the 1-year study. Renal histology, and cardiac and plasma metabolomics and mitochondrial function in the heart and kidney were evaluated at 1 year. Measured glomerular filtration rates (GFR) were similar between male and female mice throughout the 1-year study period. One year after AKI, female mice had preserved diastolic function, normal blood pressure, and preserved levels of cardiac ATP. Compared to males, females demonstrated pathway enrichment in arginine metabolism and amino acid related energy production in both the heart and plasma, and glutathione in the plasma. Cardiac mitochondrial respiration in Complex I of the electron transport chain demonstrated improved mitochondrial function in females compared to males, regardless of AKI or sham. This is the first study to examine the long-term cardiac effects of AKI on female mice and indicate that there are important sex-related cardiorenal differences. The role of female sex in cardiovascular outcomes after AKI merits further investigation.